Active infection and morphometric study of Trypanosoma evansi among horses in Peninsula Malaysia - Elshafie, E. I.; Abdullah Sani, Rehana; Hassan, Latiffah; Kumar Sharma, Reuben Sunil; Fateh Mohamed, Bashir Ahmad; Abubakar, I. A. (Malaysian Society of Parasitology and Tropical Medicine, 2013)
Apart from occasional reports of clinical disease affecting horses, there is no information about Trypanosoma evansi in horses in Peninsula Malaysia. Thus, a cross-sectional study was conducted in eight states in Peninsula Malaysia to determine the active presence of T. evansi in horses. A total of 527 blood samples were obtained and examined by haematocrit centrifugation technique (HCT), Giemsa-stained thin blood smear (GSS), morphometric measurements, polymerase chain reaction (PCR) and cloning of PCR products. The results showed an overall parasitological prevalence of 0.57% (3/527, CI: 1.6-0.19%) with both HCT and GSS. Morphometric study revealed the mean total length of the trypanosomes including the free flagellum was 27.94 ± 2.63 µm. PCR successfully amplified a trypanosome specific 257 bp in 1.14% of samples (6/527, CI: 2.4-0.52%) and was confirmed by nucleotide sequences. The mean packed cell volume (PCV) for the positive cases detected by HCT was lower (23% ± 7.00) compared to the positive cases detected by PCR alone in the state of Terengganu (35% ± 4.73). In conclusion, this study showed T. evansi infection occurred in low frequency in horses in Peninsula Malaysia, and anaemia coincided with parasitaemic animals. PCR is considered as a sensitive diagnostic tool when parasitaemia is undetectable. The slight lengthier mean of parasite and anaemia may indicate a virulent strain of T. evansi circulating throughout the country. Thus, it’s highly recommended to shed light on host-parasite relationship for better epidemiological understanding.